Bodies of Horror in Judges 19-21 and Evil Dead II (1987) - Matheny, Jennifer M. (The journal of religion and film, 2024)
Sam Raimi's Evil Dead II (1987), a horror film, demonstrates key thematic parallels with Judges 19-21. Evil Dead IIidentifies with the film genres of "splatter horror" and "dark comedy" with a B-movie cult classic vibe. Placing the Bible’s body horror (Judges 19) and horror film in dialogue on their own terms creates an intertextual dialogue that can be fruitful when dealing with violent biblical texts that communicate an excess state of terror (Phyllis Trible). Through the lens of postbiblical intertextuality (Marianne Grohmann and Hyun Chul Paul Kim), this paper will explore thematic parallels and connections in conversation between Evil Dead II and Judges 19-21. These intentional devices in film and text invite the viewer or observer to respond.